Delamination Detection in CFRP Stringers with A0-Mode Lamb Wave Curvature - Gaozheng Zhao; Yike Zeng; Zhenyang Yu; Kaihua Sun; Jian Chen (Sensors)
Ultrasonic detection of delamination in stringer-stiffened panels made of carbon fiber-reinforced plastics (CFRPs) presents a critical challenge due to their complex geometry, complicated properties and large size. In this work, a delamination detection method using the wavefield curvature of the A0-mode Lamb wave is proposed. Firstly, the underlying mechanism is numerically investigated to examine the interactions between the A0-mode Lamb wave and delamination at different sites of the stringer. Then, the wavefield curvature sensitive to local anomalies is revealed owing to the higher-order derivative nature. Thereafter, the proposed method is utilized to detect delamination in the fabricated CFRP specimens and the results are compared with X-ray computed tomography, confirming the feasibility and effectiveness of the proposed method. This viable method, capable of detecting delamination in larger CFRP stringers, will find great potential in the efficient non-destructive testing of CFRP structures in different applications.